2017
DOI: 10.1177/1476127016685237
|View full text |Cite
|
Sign up to set email alerts
|

Organizational strategies in the context of legitimacy loss: Radical versus gradual responses to disclosed corruption

Abstract: How do organizations respond to the loss of legitimacy in the context of disclosed corruption, and what drives the particular responses adopted? In this article, we study the organizational strategies of three multinational companies before, during, and after legitimacy loss due to disclosed organizational corruption. We explore why some multinational companies exceed regulatory expectations and choose radical strategies that substantially influence their environment by defining a new benchmark of anticorrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 76 publications
0
27
0
2
Order By: Relevance
“…The second stage of the Starbucks response went beyond mere rhetoric and had consequences in substance as Starbucks made changes in their transfer pricing and structural conditions. This situation further demonstrated that Starbucks was experiencing what Schembera and Scherer (2017) depict as a strong 'legitimacy shock', in which organizations are likely to go beyond symbolic responses and are more likely to react 'radically and instantly'. This study reveals similar dynamics and confirms the dramatic nature of the substantive changes that were associated with such responses (Schembera and Scherer, 2017).…”
Section: Contributionmentioning
confidence: 95%
See 3 more Smart Citations
“…The second stage of the Starbucks response went beyond mere rhetoric and had consequences in substance as Starbucks made changes in their transfer pricing and structural conditions. This situation further demonstrated that Starbucks was experiencing what Schembera and Scherer (2017) depict as a strong 'legitimacy shock', in which organizations are likely to go beyond symbolic responses and are more likely to react 'radically and instantly'. This study reveals similar dynamics and confirms the dramatic nature of the substantive changes that were associated with such responses (Schembera and Scherer, 2017).…”
Section: Contributionmentioning
confidence: 95%
“…This situation further demonstrated that Starbucks was experiencing what Schembera and Scherer (2017) depict as a strong 'legitimacy shock', in which organizations are likely to go beyond symbolic responses and are more likely to react 'radically and instantly'. This study reveals similar dynamics and confirms the dramatic nature of the substantive changes that were associated with such responses (Schembera and Scherer, 2017). Accordingly, the influence on organizational practices appears to be not only substantive but also irreversible because changes in tax practices cannot be reversed and were later followed up by a major restructuring to move the European headquarters to London.…”
Section: Contributionmentioning
confidence: 95%
See 2 more Smart Citations
“… O sistema de governança deve espelhar a eficácia da MNC, diminuindo os riscos morais, ao controlar seus agentes, por meio de procedimentos e rotinas que reduzam o problema da assimetria de informações (EISENHARDT, 1989), com objetivo de prevenir e combater a grande corrupção.2.4.3. Pressupostos da literatura de governança corporativa e responsabilidade social A MNC envolvida em crise pública, devido à divulgação de práticas de corrupção na mídia, adota estratégias para recuperar a reputação, reconstruir a imagem e manter sua legitimidade(BLANC et al, 2017;BLANC et al, 2019;HAUSER;HOGENACKER, 2014;PFARRER et al, 2008;SCHEMBERA;SCHERER, 2017;SROKA;SZÁNTÓ, 2018). As MNCs estabelecem valores ou princípios, procedimentos e rotinas para atender às demandas das instituições reguladoras internacionais e nacionais (BARKEMEYER; PREUSS; LEE, 2015; BARKEMEYER; PREUSS; OHANA, 2018; GORDON; MYIAKE, 2001). Esta aderência deve estar evidenciada por meio de seus códigos de conduta e relatórios anuais.…”
unclassified